Global Sagittal Spinal Compensation for Dropped Head Alignment. Issue 6 (15th March 2023) - Nishimura, Hirosuke; Endo, Kenji; Sawaji, Yasunobu; Suzuki, Hidekazu; Aihara, Takato; Murata, Kazuma; Konishi, Takamitsu; Yamauchi, Hideya; Ueshima, Tomoyuki; Yamamoto, Kengo
Abstract : Study Design: This is a retrospective radiographic study of a consecutive series of cases in patients with dropped head syndrome (DHS) at a single tertiary referral center. Objective: The aim was to clarify the compensation among parameters of spinal sagittal alignment in patients with DHS. Summary of Background Data: The treatment strategy for DHS should vary according to the types of global sagittal spinal alignment. However, theoretical evidence in consideration of spinal sagittal compensation against the dropped head condition is lacking. Materials and Methods: One hundred sixteen patients diagnosed with isolated neck extensor myopathy were enrolled. Radiographic measurements were made, including parameters of spinal sagittal alignment. The patients were divided into three groups according to sagittal spinal balance: C7SVA (sagittal vertical axis) ≥ +50 mm (P-DHS; positive imbalanced DHS), −50 mm ≤C7SVA <+50 mm (B-DHS; balanced DHS), and C7SVA <−50 mm (N-DHS; negative imbalanced DHS). Correlations among the various spinal parameters were analyzed. Results: Among all types of DHS, there was no correlation between C2-C7 angle (C2-C7A) and T1 slope. In B-DHS, other correlations among the adjacent spinal segments were maintained. In N-DHS, there was no correlation between C2-C7A and TK, and in P-DHS, there was also no correlation between TK and lumbar lordosis. Conclusions: The loss of compensation at the cervicothoracic junction was observed in all DHS types. B-DHS showed decompensation only at the cervicothoracic junction. N-DHS presented additional decompensation of the thoracic spine, and P-DHS showed decompensation between the thoracic and lumbar spine. Evaluation of global sagittal spinal balance is important for determining global spinal compensation associated with DHS and when considering treatment strategy.